Legal Schools in Islam, History of the Emergence of Legal Schools, Differences of Opinion About the Position of Legal Sources - Ade Daharis; Salma; Muchlis Bahar (Universitas Muhammadiyah Palu, 2025)
Differences of opinion among scholars in the fields of Islamic law actually occurred during the time of the Companions of the Prophet. However, these differences can still be overcome with political policies and the legality of ijmak. However, at the end of the Companion period, known as the Tabi'in period (approximately starting in 41 AH), differences of opinion could not be resolved like they were resolved during the Companion period. This is where the process of transitioning Islamic law began from a form of ijtihad which was based on the greatness of friends to a scientific and measurable process until the birth of school imams who codified the results of their legal thinking in the form of fiqh books. Ahl al-Hadith and Ahl al-ra'y are two forms of legal thought that ushered in this transition process. That period was the time when efforts to shape Islamic law began to suit societal conditions and rationality. The school of thought is the main idea or basis used by the mujtahid Imam in solving problems; or adhere to Islamic law. The emergence of the school of thought, as part of the historical process of establishing Islamic law, was neatly arranged from generations of friends, tabi'in, until it reached its golden age in the Abbasid Caliphate, but it must be acknowledged that the school of thought has made a major contribution to thinking in establishing Islamic jurisprudence law. The reasons for the differences opinion/school of thought due to differences in perception in ushul fiqh and fiqh as well as differences in interpretation or interpretation of mujtahids. Adhering to the understanding of bermahzab, due to factors Our